Answer:
The roots of the polynomial equation x^3 - 7x = 6x - 12 is 1, 3, -4 Hence option B is correct
Solution:
Given that the polynomial equation is
![x^(3)-7 x=6 x-12](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8h9asahve675arx242dpa041nzyz56rpvg.png)
We are asked to find the roots of the polynomial
![x^(3)-7 x=6 x-12](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8h9asahve675arx242dpa041nzyz56rpvg.png)
![x^(3)-7 x-6 x+12=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mglxxeorwpr221kvphvatc3l0vbhrrcnu6.png)
On solving we get,
![x^(3)-13 x+12=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3m795e5jru6d0ietoj9c7ie1ml8r5m48ni.png)
![x^(3)-12 x-x+12=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ax7aadcrmr6e2aa834cnofxd7xt2z7q4tq.png)
![\begin{array}{l}{x\left(x^(2)-1\right)-12(x-1)=0} \\\\ {x\left(x^(2)-1\right)-12(x-1)=0}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/we1oowpqawk6wrlhtrt5vnf0cxekudaobs.png)
(x-1)(x(x+1)-12)=0
(x-1)(x-3)(x+4)=0
x = 1, 3, -4
Hence the roots of the polynomial equation x^3 - 7x = 6x - 12 is 1, 3, -4 Hence option B is correct